Widening Participation in Ghana and Tanzania - Morley, Louise (International Higher Education, 2012)
?An interrogation under way is whether policies for widening participation in sub-Saharan Africa are working. That was one of the key questions addressed by the research project Widening Participation in Higher Education in Ghana and Tanzania: Developing an Equity Scorecard. Research teams found that the policies were working in the sense of increasing the overall number of students, especially women, participating in higher education. However, they found that poorer and mature students were still absent from many of the programs investigated in one public and one private university, in both Ghana and Tanzania. The universities included in the study did have quotas for students from disadvantaged backgrounds, but failed to fill them or monitor how many poorer students were participating and completing their studies. Students who did succeed, in entering university, shared helpful insights into their lived experiences.